2008
DOI: 10.1109/vetecs.2008.570
|View full text |Cite
|
Sign up to set email alerts
|

Throughput vs. Distance Tradeoffs and Deployment Considerations for a Multi-Hop IEEE 802.16e Railroad Test Bed

Abstract: Abstract-Throughput vs. distance analysis and coverage requirements are critical issues in planning wireless network deployments. With the recent availability of IEEE 802.16e and its promise of larger coverage areas for high-speed data communication, evaluating it in a real-world environment is very important to us in our ongoing study of standards based wireless technologies for the Federal Railroad Administration (FRA). In this paper, we present results obtained with our IEEE 802.16e module for NS-2, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our computer simulation efforts are designed to investigate these claims and the potential of this technology. Some of our findings are documented in [2][3][4][5]. We find that in our work it is vital to have an accurate measure of the path loss exponent for particular areas of interest.…”
Section: Introductionmentioning
confidence: 79%
“…Our computer simulation efforts are designed to investigate these claims and the potential of this technology. Some of our findings are documented in [2][3][4][5]. We find that in our work it is vital to have an accurate measure of the path loss exponent for particular areas of interest.…”
Section: Introductionmentioning
confidence: 79%
“…It can be noticed that (10), (11), (13) and (15) give the general form to obtain the breakpoint distance Z k , the maximum MAC throughput S max at a distance D, and the relay intermediate distances r i IV. CONCLUSION In this paper, we present a novel approach to obtain the optimal performance bounds for a multi-hop multi-rate WLAN as a function of distance between the relays.…”
Section: Optimum Solution For K-hopsmentioning
confidence: 99%
“…The simulation results showed that the system can detect the MAC-level problems accurately, regardless of AP density or shadowing effect. Using IEEE 802.16e module for NS-2, particularly throughput versus distance, results were obtained [13]. A quantitative analysis was conducted via extensive simulation, and the optimal modulation and coding scheme as well as channel bandwidth profiles were identified for specific distances.…”
Section: Introductionmentioning
confidence: 99%
“…It provides high datarate and large coverage with features like QoS, handover, HARQ and vehicular mobility support, making it a cost-effective and reliable solution for a wide range of applications. Our research team at the University of Nebraska-Lincoln's Advanced Telecommunications Engineering Laboratory has been studying design, implementation and simulation of difference aspects of Mobile WIMAX [2][3][4][5][6][7] with the primary objective of designing broadband solutions for the North American railroad industry. Mobile WiMAX is a good prospective standard to deliver mobile video streaming [8,9], VOIP [10] and broadcasting services [11].…”
Section: Introductionmentioning
confidence: 99%